D–π–A Dye Sensitizers Made of Polymeric Metal Complexes Containing 1, 10‐Phenanthroline and Alkylfluorene or Alkoxybenzene: Synthesis, Characterization and Photovoltaic Performance for Dye‐Sensitized Solar Cells. Issue 26 (29th July 2013) - Yu, Xiaoguang; Jin, Xueliang; Tang, Guipeng; Zhou, Jun; Zhang, Wei; Peng, Dahai; Hu, Jiaomei; Zhong, Chaofan
Abstract: Four polymeric metal complexes (P1 –P4 ) based on 1, 10‐phenanthroline metal complexes and alkylfluorene or alkoxybenzene were synthesized by the Heck coupling reaction and were developed for dye‐sensitized solar cell applications. The target dyes use alkoxybenzene or alkylfluorene as the electron donor, a C=C moiety as the π linker, and the phenanthroline derivative complex was used as the electron acceptor. Bipyridine derivatives were ancillary ligands as well as providing anchoring groups. The thermal, photophysical, electrochemical and photovoltaic properties of these copolymers were investigated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), C–V curves and I–V curves. Dye‐sensitized solar cells with these polymeric metal complexes as dye sensitizers exhibited considerable power conversion efficiencies (PCE). The dyes containing alkoxybenzenes (P3, P4 ) exhibited higher PCE values than the corresponding target polymers containing alkylfluorenes (P1, P2 ), The dyeP3 showed the maximal power conversion efficiency of 2.12 % ( J sc = 4.91 mA/cm 2, V oc = 0.69 V, FF = 62.5). In addition, the four polymers possessed excellent stabilities, and their thermal decomposition temperatures all exceeded 300 °C, indicating that these polymeric metal complexes are suitable for the fabrication processes of optoelectronic devices. Abstract : FourD– π–A polymeric dyes based on 1, 10‐phenanthroline metal complexes and alkylfluorene or alkoxybenzene units have been synthesized. These hybrid polymers exhibit properties of inorganic and organic metal complexes, which enhances their absorption of light. The polymeric metal complexes containing octyloxy‐substituted benzene exhibit better device performance than octylfluorene‐substituted polymers.